Towards an integrated approach to industry dynamics and labour mobility - Mamede, R. (2007)
Industrial dynamics and labour mobility are two fields of economic research that have developed fast in recent years, but along what are essentially separate lines. This paper shows that the processes those two fields deal with can be highly interdependent, and demonstrates the usefulness of (and the opportunity for) an integrated approach to the dynamics of industries and labour mobility. It concludes with a list of questions that inform a research agenda dedicated to such approach.